Assessment of Lecturers’ Knowledge and Readiness for Open Education Resources in Nigerian Open and Distance Learning Universities - Opateye, Johnson Ayodele; Inegbedion, Juliet Obhajajie (West African Journal of Open and Flexible Learning, 2017)
The open educational resources project has been underway for over decade now and universities are slowly adopting may be because of insufficient knowledge and readiness necessary to embrace it. This study focused on assessing the knowledge and readiness for open education resources among lecturers based on gender, academic status and areas of specialisation. A survey research design was employed on the five thousand three hundred and fifteen lecturers from five accredited distance education universities in Nigeria. Total sample used was six hundred and ninety selected using stratified sampling technique. Two research questions were answered and three hypotheses were tested. OER knowledge and readiness’ questionnaire developed by researchers with 0.79 reliability coefficient using Cronbach Alpha was the instrument for the study. Data collected were analysed using descriptive, t-test, analysis of variance and Bonferroni Post Hoc statistics. Results showed that distance learning lecturers with the rank of professors had lower knowledge of OER but possessed higher readiness to adopt OER than those in lower ranks. Female lecturers in ODL institutions were better in OER knowledge than male lecturers. Significant difference existed in OER knowledge but insignificant difference was noticed in readiness for OER. It is therefore recommended that highly ranked and male lecturers should more sensitise through training, workshops and seminars in OER. Also, creation and use of OER by lecturers should be recognised in their promotion to serve as incentive to favourably dispose to OER usage.Résumé : Le projet de ressources éducatives non-restreintes est en cours depuis plus d'une décennie et les universités l'adoptent lentement, peut-être en raison d'un manque de connaissances et de réceptivité nécessaires pour l'adopter. Cette étude s'est concentrée sur l'évaluation des connaissances et de l'état de réceptivité des enseignants aux ressources éducatives non-restreintes en fonction du sexe, du statut académique et des domaines de spécialisation. Un plan de recherche par sondage a été mené sur cinq mille trois cent quinze enseignants dans les universités agréées de l’enseignement à distance au Nigéria. L'échantillon total utilisé était de six cent quatre-vingt-dix sélectionnés à l'aide de la technique d'échantillonnage stratifié. On a répondu à deux questions de recherche et vérifié trois hypothèses. Le questionnaire sur la connaissance et l'état de réceptivité aux REN, élaboré par des chercheurs avec un coefficient de fiabilité de 0,79 à l'aide de Cronbach Alpha, a été l'instrument de l'étude. Les données recueillies ont été analysées à l'aide d'une analyse descriptive, d'un t test, d'une analyse de variance et de statistiques Post Hoc de Bonferroni. Les résultats ont montré que les enseignants de l'enseignement à distance ayant le rang de professeurs connaissaient moins bien les REN, mais ils étaient plus disposés à les adopter que les enseignants de rang inférieur. Les enseignantes des établissements de l'enseignement à distance étaient mieux informées sur les REN que les enseignants. Il y avait une différence significative dans la connaissance des REN, mais une différence insignifiante a été constatée dans l'état de réceptivité à l'utilisation des REN. Il est donc recommandé de sensibiliser les hommes enseignants de haut niveau à regard de REN par le biais de formations, d'ateliers et de séminaires. En outre, la création et l'utilisation des REN par les enseignants devraient être reconnues dans leur avancement pour servir d'incitation à ceux qui sont favorables à l'utilisation des REN.
Keywords: Open education resources; Lecturers’ readiness; Lecturers’ Knowledge; Academic status; Area of specialisation; Gender